EFEKTIVITAS METODE DEMONSTRASI PADA MATA PELAJARAN UBUDIYAH UNTUK MENINGKATKAN RELIGIUSITAS SISWA: LITERATURE REVIEW - Ahmad Chafidut Tamam; Abdul Muhid (Kariman: Jurnal Pendidikan Keislaman, 2022)
One thing that really contributes greatly to learning success is the selection of the right method according to the material being taught. Learning methods are certain methods used by teachers or educators to create learning experiences that are fun, useful, and develop aspects of skills for students. Religiosity is the commitment of a Muslim in carrying out religious activities with full appreciation. This study aims to describe the effectiveness of the application of the demonstration method to increase student religiosity in the local content of ubudiyah. The results showed that previous research related to the effectiveness of the demonstration method showed that the demonstration method was very relevant, effective and efficient when used in PAI learning, especially in practical materials, such as praying, slaughtering, and caring for corpses.